(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2003)
Sophism of "globalization" in worldwide market entropic. The author intends to demonstrate that the theoretical models whose object implicates the politics, in the Sociology, in the Political Theory, and in the Law, exclude the sensu stricto scientific knowledge sharing the same repertoire of the common knowledge in the mythical belief of the "order" in the territorial and extraterritorial markets, with their fictional succedaneous of good / evil as "globalization". On the politics object, the author will superpose the semiotics-physics complex method (1) of Semioselogy, including of the Physics phenomenology (Heisenberg, Bohr, Lao Tzy), of Signology (Peirce), and of the Progmatic Operational Instrument (Modesto), and (2) of Hominilogy (Modesto), to describe the extraterritorial and territorial worldwide economic market, in its chance and entropic dominance, in relation to the slogan of the "globalization", transmitted by the political market among concurrent pluridominances of the economic market. The author also intends to describe that relationship between the economic market and the political market and to demonstrate the distance between that slogan of the economic market, travestied of “argument” by the superposition of the political market and subposition of the academy, and the quantified implications between the extraterritorial and territorial economic markets, exposing the theology that founds the ecstasy of the "globalization".